The Professional and Personal Development of Private and Public Senior High School Teachers - Eugenio, Erickson T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examined the professional and personal development of private and public senior high school teachers in Jones, Isabela, Philippines. Using a descriptive survey design, 60 teachers completed questionnaires assessing their demographic profiles, 21st-century competencies, and personal and professional capabilities. The results showed high proficiency across most areas, with no significant differences between private and public school teachers. Educational attainment positively impacted professional capabilities. Teachers demonstrated strong skills in classroom management, communication, and creating a respectful learning environment. However, areas for improvement include supporting learners and adapting to technological changes. These findings highlight the importance of ongoing professional development to enhance teaching practices and student outcomes. Key implications include the need for collaborative learning experiences, technology integration, and curriculum design that incorporates real-world applications. The recommendations emphasize personalized professional development programs, reassessing assessment methods, and creating inclusive learning environments. This study contributes to understanding teacher development in the Philippine context, particularly by comparing the private and public sectors. This underscores the critical role of teacher motivation and enthusiasm in fostering student engagement. Future research should explore the long-term impacts of professional development initiatives and examine rural-urban disparities in teacher capabilities. Overall, the study advocates for a holistic transformation of educational practices to better equip teachers to meet 21st-century challenges and improve students’ learning experiences.